Effects of Air Impingement Jet Drying on Drying Kinetics and Some Quality Attributes of Strawberry Slices - M Rad (Ferdowsi University of Mashhad, 2021)
Introduction Strawberry plays an important role in human health because of its micronutrients and natural antioxidant content. Increasing storage time and decreasing microbial processes, weight and volume, and eventually facilitating export, has bolded the need for drying this product. The most common drying method is sun drying. This technique requires large areas and lengthens the time to complete the process which is undesirable economically. Furthermore, the final product may be contaminated by dust and insects, and the exposure to solar radiation results in color deterioration. In order to improve the quality, traditional sun drying techniques can be replaced by a more rapid and efficient drying method such as hot-air drying. In recent years air impingement technology has got more attention in the field fruit slices drying due to high heat and mass transfer, decreasing drying time and increasing product quality. The objectives of this study were to investigate the effects of drying conditions on the drying kinetics and quality characteristics including the rehydration ratio of the strawberry slices in an air impingement jet dryer. Materials and Methods An air jet impingement dryer with controllable temperature, air velocity, and the relative nozzle-to-product distance (H/D) was used in this study. The experiments were conducted under different temperatures (45, 55, and 65°C), air velocities (6, 9, and 12 m s-1) and H/D ratios (4, 5, 6, 7, and 8). The initial moisture content, effective moisture diffusivity, activation energy, and rehydration ratio were evaluated. Results and Discussion The effects of drying temperature and air velocity on the moisture ratio and the drying rate are shown in Figs 2 and 3. As it can be seen, the moisture ratio of strawberry slices decreased with the increase of drying time. The analysis of variance for drying time indicated that increasing drying temperature and air velocity could reduce the drying time.  In addition, the effect of drying temperature on drying time was more significant than that of the air velocity.  It is clear that the drying rate decreased with moisture content. There was a rapid decrease in drying rate during the initial period and slow decrease at the later stages of the drying process. It is also found that the drying process generally took place in the falling rate period. It is observed that the moisture ratio decreased as H/D ratio fall. The response of drying time was affected significantly (p < 0.05) by H/D ratio. The effective moisture diffusivity increased with increasing drying temperature and air velocity. Based on the results reported in this study, the Wang and Singh model with the lowest Root Mean Square Error (RMSE=0.02) and the highest Coefficient of determination (R2=0.996) provided the best fit to describe the experimental drying data of strawberry slices. The statistical analysis shows that drying temperature and air velocity have significant (p < 0.01) effect on the rehydration ratio (RR) of slices, while the interaction effect was not significant. The means comparison shows that the RR of dried slices decreased as drying temperature and air velocity rose. H/D ratio significantly (1%) affected rehydration ratio. The means comparisons shows that the rehydration ratio increased when H/D value varied from 4 to 8. Also, the results of color change represented that color change of dried samples decreased with increase of temperature and air velocity and increased with increase of the H/D ratio. Conclusions a) Increasing drying temperature and air velocity dropped the drying time. In addition, the effect of drying temperature on drying time was more significant than that of the air velocity. b) A constant rate period was not observed in drying of strawberry slices and the whole process of strawberry slices was carried out in the falling rate period. c) The moisture ratio decreased as H/D ratio dropped, which in turn resulted in saving drying times. d) The Wang and Singh model was found to be the best model to describe the drying kinetics of strawberry slices. e) The effective moisture diffusivity of strawberry slices ranged from 1.62×10-10 to 3.24×10-10 m2 s-1. f) The values of activation energy of strawberry slices were found to be 12.88, 15.055 and 16.746 kJ mol-1 for air velocities of 6, 9 and 12 m s-1, respectively. g) The rehydration ratio of dried slices dropped as the drying temperature and air velocity rose and increased with increase of the H/D ratio. h) The color change of dried samples decreased with the increase of temperature and air velocity and increased with the increase of the H/D ratio.